P497Arrhythmic burden in patients with filamin C (FLNC) truncating variant associated cardiomyopathy. (18th June 2020) - Zupan Meznar, A; Zizek, D; Breskvar Kac, U D; Writzl, K; Jan, M; Toplisek, J; Baraga, M; Sinkovec, M
Abstract: Background: Truncating variants in FLNC gene are associated with an overlapping phenotype of arrhythmogenic and dilated cardiomyopathy. There are reports of high arrhythmia propensity with sudden cardiac death (SCD) often being the first symptom of the disease. It has been suggested that the current European guidelines primary prevention (PP) recommendation about implantable cardioverter-defibrillator (ICD) implantation might not be applicable in these patients and that earlier intervention should be considered. Purpose: We sought to investigate the arrhythmic burden in FLNC truncation carriers in our centre. Methods: Adult FLNC truncation carriers diagnosed in our centre between the years 2018 and 2019 were included in the study. We retrospectively analysed clinical data, and ICD follow-up reports in the cohort. Patients implanted with an ICD were divided in 3 groups: group A (secondary prevention ICD implantation), group B (PP indication according to the current guidelines – left ventricular ejection fraction (LVEF) below 35%) and group C (early PP– FLNC truncation carrier, LVEF < 50% and late gadolinium enhancement on cardiac magnetic resonance). We report the number of patients experiencing SCD and the number of appropriate and inappropriate ICD therapies per group. Results: Twenty-four adult patients from 3 different families with three distinct FLNC truncating variants were identified. Ten (42%) were male; the average age was 45 ± 14 years. There were 3 (13%) SCDs in one family (2 male and one female, 29-42 years old) and two (8%) aborted SCDs in the remaining two families (one male and one female, 66 and 51 years old). Altogether eleven (46%) patients were implanted with an ICD. There were three patients in group A (2 aborted SCDs and 1 sustained ventricular tachycardia (VT)), two patients in group B and six patients in group C. Average ICD follow-up times were 42, 48 and 6 months for groups A, B and C, respectively. Eight appropriate ICD therapies occurred in 3 patients (27%). In group A, there were four sustained VT episodes successfully converted with an anti-tachycardia pacing (ATP) in two patients (67%); the average time to first therapy was 33 months. In group B, there was one appropriate shock for ventricular fibrillation (VF), and three sustained VT episodes in one patient (50%), time to first therapy was 60 months. After six months follow-up, there were no appropriate therapies registered in group C. Two patients (18%) experienced inappropriate shocks due to sinus tachycardia, one in group A and one in group C. Conclusion: One-fifth of FLNC truncation carriers in our cohort experienced SCD. When patients received an ICD according to the current guidelines, majority experienced appropriate ICD therapy. Further clinical studies with longer follow-up will be needed to define appropriate risk stratification and optimal timing for prophylactic ICD intervention in these patients.